Pompeii, the body, and the imprint of the ancient world. Issue 3 (3rd July 2017) - Thomas, Sophie
Abstract: Archaeological discoveries at Pompeii and Herculaneum—those long-buried sites of distant antiquity—inspired historical reconstitution, both material and imaginary, in a variety of print forms. Some of these acted as paper museums, gathering and presenting objects, while others engaged with the site in imaginative terms, giving rise to a body of work (text, image, spectacle) that attempted to recover the contours of the ancient world in and for the present. This essay focuses on Pompeii in particular, as a site fixed in time, both destroyed and preserved by the eruption of Vesuvius, and examines how the poetics of the imprint and of the cast—most notably in relation to human remains—animates a variety of nineteenth-century texts. The preserved impressions of bodies, footprints, and cart-tracks offer suggestive points of contact, both literal and metaphorical, with things irrevocably past and lost. I argue that the imprint of Pompeii encourages a richly self-reflexive exploration of the possibilities and the fragility of print, in our efforts to re-mediate the materiality of the ancient world.